2017
DOI: 10.1063/1.4990285
|View full text |Cite
|
Sign up to set email alerts
|

Resonant and resistive dual-mode uncooled infrared detectors toward expanded dynamic range and high linearity

Abstract: This paper reports an uncooled infrared (IR) detector based on a micromachined piezoelectric resonator operating in resonant and resistive dual-modes. The two sensing modes achieved IR responsivities of 2.5 Hz/nW and 900 μdB/nW, respectively. Compared with the single mode operation, the dual-mode measurement improves the limit of detection by two orders of magnitude and meanwhile maintains high linearity and responsivity in a higher IR intensity range. A combination of the two sensing modes compensates for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…TCF is usually an intrinsic property of materials that is dependent on the growth conditions. The TCF of the proposed device is comparable with previously reported values [3,5,36]. Figure 2c also shows that the proposed sensor has a large linear dynamic range, which is beneficial for practical applications.…”
Section: Characterizationsupporting
confidence: 87%
See 3 more Smart Citations
“…TCF is usually an intrinsic property of materials that is dependent on the growth conditions. The TCF of the proposed device is comparable with previously reported values [3,5,36]. Figure 2c also shows that the proposed sensor has a large linear dynamic range, which is beneficial for practical applications.…”
Section: Characterizationsupporting
confidence: 87%
“…The responsivity can also be expressed as 110 Hz/nW over the sensing area of 15,000 μm 2 . This result indicates a much higher sensitivity than those of previous reports [3,5]. The results also exhibit good linearity and a large dynamic range.…”
Section: Characterizationsupporting
confidence: 38%
See 2 more Smart Citations
“…As the humidity sensitive layer, PI enhanced the humidity sensitivity to +67.3 kHz/%RH (64 ppm/%) between 15%RH and 85%RH with a sufficient Q (>200), which is 39 times higher than the sample without PI film. Inspired by the improved sensor performance by two-parameter detection, such as resonant frequency and resistance [ 29 ], resonant frequency and reflection coefficient S 11 [ 30 ], we further investigated the reflection coefficient S 11 response of the PI-FBAR humidity sensor [ 25 ]. Results showed that an ultra-high average humidity sensitivity of 0.044 dB/%RH (2095 ppm/%RH) was achieved, and the sensitivity at 20% low relative humidity reached 0.075 dB/%RH (3571 ppm/%RH), which is more than two orders of magnitude higher than that of the resonant frequency response.…”
Section: Introductionmentioning
confidence: 99%